Fatores determinantes da transparência dos poderes executivos municipais brasileiros a partir do índice nacional da transparência do MPF - Celestino, Égon José Mateus (2018)
This study aims to analyze the factors to the transparency of Brazilian municipal executive based on Índice Nacional da Transparência from Ministério Público Federal. To this, it uses empirical-analytical methodology applied to an aleatory data from this study with 525 Brazilian cities. In this case, the independent variable is Índice Nacional da Transparência from Ministério Público Federal and other explicative variable like social, economic and politic dimension. It has as base an econometrical model of regression Tobit, used to verify the best variables with an explicative capacity to the occurrence of this phenomenon of the best practices of public transparency. Results point that cities from South and Southwest show best levels of transparency and accountability comparing to the cities from North, Northwest and Center-west, this phenomenon comes from the best indicators from Índice de Desenvolvimento Humano related to cities in the South and Southwest regions from Brazil. It concludes that the determining factors for better levels of transparency in Brazilian municipalities are the political factors only the educational level of the mayor, the economic factors, the IDH and consolidated debt variables and the social factors the variables Education, Urbanization and Demographic Density, being then social factors the best explanatory estimators for Brazilian municipal public transparency. The contribution of this research consists in the validation of a model to determine a predictive variable to explain the phenomenon Brazilian municipal public transparency based on institutional evaluation from Ministério Público Federal.